The association between food insecurity and subjective wellbeing in Sub-Saharan Africa. (28th October 2019) - Sulemana, Iddisah; James, Harvey S.
Although hunger levels across the globe have generally declined in the last two decades, food insecurity remains a global public policy concern. Moreover, the majority of the world's most food insecure people reside in South East Asia and Sub-Saharan Africa. These regions are also among the world's regions with some of the lowest scores of subjective wellbeing, another public policy priority engaging world leaders. In this study, we examine association between food insecurity and subjective wellbeing in Sub-Saharan Africa. Using data from the Wave 6 of the World Values Survey for five countries, our results from OLS regressions reveal that food insecure people are significantly less likely to report being satisfied with their lives. A potential policy implication of our findings is that by reducing food insecurity public policy in Sub-Saharan Africa could improve subjective wellbeing.